Dietary Behavior And History Of Nausea And Vomiting With Pregnancy Anemia - Mudlikah, Siti; Handajani, Diani Octaviyanti; Nabila, Faza; Triastin, Suci Aulia; Widiyawati, Wiwik; Nadhiroh, Aim Matun (JKM (Jurnal Kebidanan Malahayati), 2024)
Latarbelakang: Prilaku kebiasan konsumsi makan yang kurang baik tidak dapat memenuhi kebutihan angka kecukupan gizi. Jumlah konsumsi makan dan jenis makan yang tidak sesuai gizi seimabng dapat berakibat gizi kurang, defesiensi zat besi dan kekurangan zat besi pada makanan. Mual muntah kehamilan memperburuk asupan nutrisi dan rawan beresiko terjadi anemia defesiensi zat besi. Tujuan penelitian untuk mengetahui factor prilaku konsumsi makan dan riwayat mual muntah  dengan anemia kehamilan.Metode: Penelitian ini menggunakan desain Analitik  Uji Lamda dengan rancangan cross sectional untuk mengetahui hubungan variable independen dengan dependen. Populasi berjumlah 40 orang. Teknik sampling: total sampling. Instrumen kuesioner data jumlah makan, data jenis makan dan riwayat mual muntah diperoleh dari wawancara. Data anemia diperoleh dari buku KIA hasil pemeriksaan hemoglobinHasil::Prilaku kebiasaan konsumsi jumlah makan ibu hamil ≤ 2kali sehari terdapat anemia sedang 6 orang (600%), dan anemia berat 2 orang (100%). Prilaku konsumsi gizi tidak seimbang mengalami anemia berat 2 orang (100%), anemia sedang 10 orang (100%), anemia ringan 6 orang (75%)Kesimpulan::tidak ada hubungan jumlah konsumsi makan dengan anemia, ada hubungan jenis konsumsi makan  gizi seimabnag dengan anemia dan ada hubungan mual muntah dengan anemia pada kehamilan.Saran: Prilaku kebiasaan jumlah konsumsi makan yang cukup dan jenis makan gizi seimbang dapat mencegah terjadinya mual muntah berlebih dan anemia pada kehamilan. Kata Kunci: Jumlah Makan, Jenis Makan, Mual Muntah, Ibu Hamil ABSTRACT Introduction: Suboptimal dietary practices can lead to a failure in meeting the necessary nutritional demands. Insufficient food consumption and the intake of nutritionally imbalanced meals can culminate in malnutrition, iron deficiency, and a scarcity of iron in one’s diet. Pregnancy-induced nausea and vomiting can further deteriorate nutritional intake, thereby escalating the risk of iron deficiency anemia. The objective of this research is to discern the association between dietary behavior and a history of nausea and vomiting in relation to anemia during pregnancy.Methodology: This research employs an Analytical Lambda Test design with a cross-sectional framework to ascertain the relationship between independent and dependent variables. The study population comprises 40 individuals. A total sampling technique was utilized. Data pertaining to meal frequency, types of meals, and a history of nausea and vomiting were gathered through questionnaires. Anemia data were extracted from the KIA book’s hemoglobin examination results.Findings: Pregnant women who consume meals ≤ 2 times per day exhibit moderate anemia in 6 individuals (600%), and severe anemia in 2 individuals (100%). Those with unbalanced nutritional consumption experience severe anemia in 2 individuals (100%), moderate anemia in 10 individuals (100%), and mild anemia in 6 individuals (75%).Conclusion: There is no discernible correlation between meal frequency and anemia. However, a correlation does exist between the consumption of nutritionally balanced meals and anemia, as well as between nausea and vomiting and anemia during pregnancy.Recommendation: Sufficient meal frequency and the consumption of nutritionally balanced meals can mitigate excessive nausea and vomiting, and prevent anemia during pregnancy. Keywords: Meal Frequency, Type of Meal, Nausea and Vomiting, Pregnant Women